The Assisted Dying Bill and the role of the physician. Issue 8 (9th January 2015) - Mullock, Alexandra
Abstract : This article explores the role of the physician in the Assisted Dying Bill, which is currently progressing through the House of Lords. The Supreme Court decision in Nicklinson and Others has alerted Parliament to the possibility that the current prohibition against assisted suicide may breach Article 8 of the European Convention in relation to the right to choose how to end one's life. In this article, the role of healthcare professionals in the proposed legalisation of physician-assisted suicide is examined, together with consideration of key ethical concerns over who might be permitted to access assisted dying. Whether the proposed law presents an ethically sound alternative to the current prohibition against assisting in suicide is not clear, but Parliament must now respond in order to address human rights issues and the call to legalise medically assisted suicide.